Determination of career preferences among marine science students through discriminant analysis - Umam, Khairul; Mastura, Ayu; Ansari, Marzuki; Nurita, Fonna; Rahayu, Latifah; Yuni, Cut; Ramadhan, Riski (Geuthèë Institute, Aceh, 2025)
The process of selecting a profession frequently poses a challenge for students transitioning into the workforce, including those in Marine Science. This decision necessitates careful consideration due to its direct correlation with their career trajectory and future prospects. This research aims to predict the professional preferences of Marine Science students towards careers as Conservation Experts, Environmental Impact Analysts, and Aquaculture Technicians, based on their academic course grades. This study employs a descriptive quantitative approach using literature research. The population of this research consists of Marine Science students from the 2020 cohort. A sample of 50 students was selected using simple random sampling techniques. Data were collected through documentation techniques, specifically student transcript records, and analyzed using Fisher's discriminant analysis with SPSS to formulate predictive functions. The results indicate that the formulated discriminant functions can accurately predict professional preferences based on course grades, achieving an accuracy rate of 88%. This high accuracy rate suggests that the derived discriminant function model has the potential to serve as a valuable tool for Marine Science students in making informed career decisions that align with their academic abilities, thereby minimizing uncertainty in determining suitable career paths.